2007
DOI: 10.1007/s00224-006-1313-z
|View full text |Cite
|
Sign up to set email alerts
|

Robust Polynomials and Quantum Algorithms

Abstract: We define and study the complexity of robust polynomials for Boolean functions and the related fault-tolerant quantum decision trees, where input bits are perturbed by noise. We compare several different possible definitions. Our main results are• For every n-bit Boolean function f there is an n-variate polynomial p of degree O(n) that robustly approximates it, in the sense that p(x) remains close to f (x) if we slightly vary each of the n inputs of the polynomial.• There is an O(n)-query quantum algorithm tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 17 publications
2
44
0
Order By: Relevance
“…Together with inequality (14), this leads to the bound on the minimal evolution time T , as stated in the main result (8).…”
Section: Runtime Lower Boundmentioning
confidence: 56%
See 1 more Smart Citation
“…Together with inequality (14), this leads to the bound on the minimal evolution time T , as stated in the main result (8).…”
Section: Runtime Lower Boundmentioning
confidence: 56%
“…In quantum query algorithms two classes of noise models have been considered. One class of noise model considers coherent errors [8,9], whereas the other class models errors in terms of either dephasing or bit-flip errors [4][5][6][7]10]. For the latter class, the quadratic speedup of Grover's algorithm vanishes and the runtime assumes a linear scaling [4].…”
Section: Introductionmentioning
confidence: 99%
“…It is still unknown what worst-case success probability in computing f ⊗k can be achieved in general, when the number of queries allowed is αR 2 (f )k for α ≫ 1. The corresponding question in the quantum query model was settled by [BNRdW07]. As mentioned earlier, O(R 2 (f )k log k) queries always suffice to compute f ⊗k with high success probability; work of [FRPU94] implies that we cannot do better than this by using a bounded-error randomized algorithm for f in a black-box fashion.…”
Section: Dpts For Dynamic Interactionmentioning
confidence: 99%
“…The proof details in [33] show that the procedure is still expected to make progress, and with high probability finds all differences after O(n) queries. 8 This algorithm implies that we can compute, with O(n) queries and error probability ε, any Boolean function f : {0, 1} n → {0, 1} on ε-bounded-error inputs: just compute x and output f (x).…”
Section: Theorem 43 (Bnrw)mentioning
confidence: 99%
“…Even more surprisingly, the only way we know how to construct such robust polynomials is via the connection with quantum algorithms. Based on the quantum search algorithm for bounded-error inputs mentioned in Section 2.3, Buhrman et al [33] showed the following:…”
Section: Robust Polynomialsmentioning
confidence: 99%